When students become teachers: training period, research and teaching practice in the formation of indigenous teachers (Práxis Educativa, 2013)
The main traineeship theme in the Indigenous Teachers Training Course at the Federal University of Amazonas is one of the most important challenges in the college training of indigenous teachers. Since indigenous university students are already teachers in their villages, current investigation endeavors to answer the following questions: What kind of activities will characterize this training and which will compose the teachers' formation? How may research and teaching practice be articulated so that efforts and results may contribute towards teacher training and indigenous schools? Current research focuses on the experience of the Mura Class which is in its final year and finishing its traineeship. Traineeship has been a space-time opportunity for reflection and activities on the school and on the teaching practice to highlight teachers' training, qualify their professional insertions and, consequently, the work of the indigenous school. Keywords: Indigenous teachers' training. Traineeship. Research. Teaching practice.